MENGGUGAT HADITS MISOGINI (Sebuah Upaya Membebaskan Posisi Kaum Hawa) - Suyatno (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2009)
Main factor of marginalization in social, cultural, educational and political living isn’t only mistake thought or mind set toward women but also becouse of being supported by holistical texts which are poor critical interpretations toward Al-qur’an verses and deeds of prophet Muhammad. This writing aims to analize some misogini deeds which deem that women are placed as the second human who are unappropriate in entering men stage, so discoursed interpretations have consequence for marginalizing women into the edge of women deadlock in giving voice at their rights and duties, refering to the historical facts, on mattes pertaining to prophet Muhammad age showed that women weren’t as people thought about women living without getting their rights and duties as men ones, other wisw on the real facts, they struggled together with men to acquire rights and duties equally and to avoid discrimination as an impact of sex and gender gaps.